Fire [videorecording (DVD)] - Mehta, Deepa, 1949-; Mehta, Deepa, 1949-; Mehta, Deepa, 1949-; Bedi, Bobby; Azmi, Shabana, 1950-; Das, Nandita; Kharbanda, Kulbhushan (International cinema (DVD videodiscs), 1998)
Banned in India, this film was the first to confront lesbianism in that country. In a barren, arranged marriage to an amateur swami who seeks enlightenment through celibacy, Radha's life takes an irresistible turn when her beautiful young sister-in-law seeks to free herself from the confines of her own loveless marriage.